Honoring the Voice of the Client in Clinical Social Work Practice: Negotiating with Epistemic Injustice. Issue 1 (26th October 2018) - Lee, Eunjung; Tsang, A Ka Tat; Bogo, Marion; Johnstone, Marjorie; Herschman, Jessica; Ryan, Monique
Abstract: Epistemic injustice occurs when therapists implicitly and explicitly impose professional and institutional power onto clients. When clients have a diagnosis of schizophrenia, this very fact further complicates and highlights the power disparity within the helping relationship. Inspired by the work of critical philosopher Miranda Fricker on epistemic injustice, and using critical theories of language and knowledge, this article analyzes audiotaped session transcripts between a client with a history of psychosis and a social worker in an outpatient mental health agency. Findings illustrate two main discursive interactional patterns in everyday clinical social work encounters: (1) how the therapist's utterances claim disciplinary power and construct the client's testimony in alignment with an institutional agenda, while pre-empting the client's lived experience; and (2) how the client, though actively resisting, is managed to perform the identity of being a mentally ill person. The authors close with suggestions of how to avoid these mishaps and work toward epistemic justice in mental health practice.